The History of Urbanization in Java Island: Path to Contemporary Urbanization - Yustina Octifanny (TATALOKA, 2020)
The paper presents the historical analysis of the spatial transformation and emerging urban reality in Java Island. The historical approach used to understand the urbanization dynamics from the year 1200 until the present time. The study passes through important historical events: early Archipelago, precolonial, colonial state, late colonialization, Japanese occupation, Indonesia’s independence, Indonesia’s democratic experiment, guided democracy, new order, fall of the new order, and post-Suharto era, in which the history of urbanization pattern is also visualized on the map. From a long time frames the colonial state, new order, and the post-1997 financial crisis are the most important influence for Java’s urbanization. From the study, it reveals that the urbanization in Java Island has undergone a series of events that made the urban population contracted or expanded; hence its centers moved to different places. The study also underlines the influence of colonial and economic crises which made Java, and particularly Jakarta, to emerge as the epicenter of urbanization in Indonesia, as Jakarta’s urban development was further enhanced after Indonesia’s independence.